Is impeded root growth related to the occurrence of rubber tree Trunk Phloem Necrosis (TPN)?: preliminary results from NE Thailand - Pierret, Alain; Doussan, C.; Pages, L.; Do, F. C.; Gonkhamdee, S.; Maeght, J.L.; Chintachao, W.; Nandris, D. (2007)
This paper presents the results of a pilot project aimed at unravelling putative links between the occurrence of Trunk Phloem Necrosis (TPN) and impeded root system development in a small rubber tree (RRIM 600) plantation of NE Thailand. To investigate as many root parameters as possible, our methodology included a wide range of techniques: destructive sampling, root mapping, rhizolocation, architectural characterisation of coarse woody roots, and electrical measurements by capacitance and earth impedance. We found that under the environmental conditions that prevail in NE Thailand, there is no relationship between most of the root parameters we measured and TPN, at least within the first meter of the soil profile. This result contrasts with observations previously made in western Africa. However, we found that at a soil depth of ~25 cm where maximum soil bulk density is generally observed, Healthy (H) trees can grow roots of significantly higher Specific Root Length (SRL) than those affected by TPN. The next phase of this work which is part of a multidisciplinary programme on TPN, will therefore focus on root morphological descriptors such as SRL and on the analysis of the deeper parts of rubber tree root systems.